2021
DOI: 10.7759/cureus.16679
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Medical Questionnaire and Influenza Rapid Test Positivity: Subjective Pretest Probability, “I Think I Have Influenza,” Contributes to the Positivity Rate

Abstract: IntroductionRapid influenza diagnostic tests (RIDTs) are considered essential for determining when to start influenza treatment using anti-influenza drugs, but their accuracy is about 70%. Under the COVID-19 pandemic, we hope to refrain from performing unnecessary RIDTs considering droplet infection of COVID-19 and influenza. We re-examined the medical questionnaire's importance and its relationship to the positivity of RIDTs. Then we built a positivity prediction model for RIDTs using automated artificial int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The current study found that combining interviews and physical examination was important for predicting influenza test results [12]. While similar studies have been available to date, they have focused solely on symptoms, with only a few studies having analyzed a combination of interviews and physical examination [12,13].…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The current study found that combining interviews and physical examination was important for predicting influenza test results [12]. While similar studies have been available to date, they have focused solely on symptoms, with only a few studies having analyzed a combination of interviews and physical examination [12,13].…”
Section: Discussionmentioning
confidence: 66%
“…In particular, interviews and physical examinations may preclude the need for invasive RIDTs among infants and reduce medical expenses [12]. Our study revealed that careful interviews and examination can predict RIDT results, highlighting their importance in clinical practice.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations